Holes in Bayesian statistics*We thank the participants of the Bayesian inference in subatomic physics workshop and two anonymous reviewers for helpful discussion and the National Science Foundation, Office of Naval Research, and Institute for Education Sciences for partial support of this work. (10th December 2020) - Gelman, Andrew; Yao, Yuling
Abstract: Every philosophy has holes, and it is the responsibility of proponents of a philosophy to point out these problems. Here are a few holes in Bayesian data analysis: (1) the usual rules of conditional probability fail in the quantum realm, (2) flat or weak priors lead to terrible inferences about things we care about, (3) subjective priors are incoherent, (4) Bayesian decision picks the wrong model, (5) Bayes factors fail in the presence of flat or weak priors, (6) for Cantorian reasons we need to check our models, but this destroys the coherence of Bayesian inference. Some of the problems of Bayesian statistics arise from people trying to do things they should not be trying to do, but other holes are not so easily patched. In particular, it may be a good idea to avoid flat, weak, or conventional priors, but such advice, if followed, would go against the vast majority of Bayesian practice and requires us to confront the fundamental incoherence of Bayesian inference. This does not mean that we think Bayesian inference is a bad idea, but it does mean that there is a tension between Bayesian logic and Bayesian workflow which we believe can only be resolved by considering Bayesian logic as a tool, a way of revealing inevitable misfits and incoherences in our model assumptions, rather than as an end in itself.